2022
DOI: 10.1177/00220345211062049
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Deficiency Underlies the Etiology of Midfacial Defects

Abstract: Embryonic craniofacial development depends on the coordinated outgrowth and fusion of multiple facial primordia, which are populated with cranial neural crest cells and covered by the facial ectoderm. Any disturbance in these developmental events, their progenitor tissues, or signaling pathways can result in craniofacial deformities such as orofacial clefts, which are among the most common birth defects in humans. In the present study, we show that Rdh10 loss of function leads to a substantial reduction in ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…cNCCs are specified at the dorsal margins of the anterior neural folds, undergo epithelial-to-mesenchymal transition, migrate extensively, and then rapidly proliferate to form the majority of the connective tissue of the head and face. Disruptions in cNCC migration and proliferation contribute to facial malformations and dysmorphology [11; 54]. While not impacting cNCC migration, we found that addition of FREM1 to cNCCs resulted in a concentration-dependent increase in proliferation (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…cNCCs are specified at the dorsal margins of the anterior neural folds, undergo epithelial-to-mesenchymal transition, migrate extensively, and then rapidly proliferate to form the majority of the connective tissue of the head and face. Disruptions in cNCC migration and proliferation contribute to facial malformations and dysmorphology [11; 54]. While not impacting cNCC migration, we found that addition of FREM1 to cNCCs resulted in a concentration-dependent increase in proliferation (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…cNCCs are specified at the dorsal margins of the anterior neural folds, undergo epithelial‐to‐mesenchymal transition, migrate extensively, and then rapidly proliferate to form the majority of the connective tissue of the head and face. Disruptions in cNCC migration and proliferation contribute to facial malformations and dysmorphology 48,49 . While not overtly impacting cNCC migration in the scratch assay, we found that addition of FREM1 to cNCCs resulted in a concentration‐dependent increase in proliferation (Figure 5).…”
Section: Discussionmentioning
confidence: 82%
“…Disruptions in cNCC migration and proliferation contribute to facial malformations and dysmorphology. 48,49 While not overtly impacting cNCC migration in the scratch assay, we found that addition of FREM1 to cNCCs resulted in a concentration-dependent increase in proliferation (Figure 5). The concentration-dependence of this effect is notable given the regulation of Frem1 by a secreted morphogen and the spatial gradient of Frem1 expression during facial morphogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…Doctors have noticed that maternal VAD patients presented with microphthalmia, blindness (Chakraborty and Chandra 2021), and bone deformities, which could result in morbidity (Williams and Bohnsack 2019). Several genetic RA deficiency models that were constructed have exhibited midfacial cleft (Wu et al 2022), nasal abnormality, and eye defects (Duester 2008). Nevertheless, although VAD patients showed an induction in the risk of osteopenia, osteoporosis, and severe craniofacial skeletal disorders (Conaway et al 2013), how retinoid signaling regulates craniofacial bone development and metabolism remains unclear, as well as the pathogenesis of VAD craniofacial skeletal deformity.…”
Section: Introductionmentioning
confidence: 99%